Management of a Retained Bullet in the Corpora Cavernosa after a Civilian Gunshot Injury: A Rare Scenario - Ali Abdel Raheem; Ibrahim Alowidah; Mohamed Almousa; Mohamed Alturki (Journal of Trauma and Injury)
A 24-year-old man presented to King Saud Medical City emergency department with a retained bullet in his penis following a civilian exchange of gunfire. After an initial assessment, the patient was taken to the operating room. Penile exploration was performed, the bullet was extracted successfully, and the corpora cavernosa were repaired properly. A 6-week follow-up showed full healing with preservation of erectile function. Immediate surgical intervention is mandatory as the primary treatment for penile gunshot injury to ensure proper anatomical and functional recovery.